COMPARISON OF BODY WEIGTH INFANTS AGED 6 TO 12 MONTHS IN EXCLUSIVE AND NON-EXCLUSIVE BREASFEEDING - Agus Sulistyowati; Dini Prastyo Wijayanti; Annisa, Faida (Nurse and Holistic Care, 2023)
Background: Breast milk is an adequate food for babies in the process of growth and development because its content such as nutrients and protective factors play a role increasing the speed of metabolism and growth thus as to reduce infant morbidity and mortality. Objective: The purpose of this study was to compare the body weight of infants aged 6-12 months between exclusive and non-exclusive breastfeeding. Methods: The method used that descriptive-comparative research design. Samples in the study were taken using the Total Sampling method. It was 70 respondents divided into two groups namely exclusive breastfeeding and non-exclusive breastfeeding. The data were taken using a Kartu Menuju Sehat (KMS, Standard Growth Charts) and analyzed using the Chi-Square test with a meaning level of 5% (α=0.05). Result: There were 21 (60%) infants with normal body weight that received exclusive breastfeeding and 19 (54.2%) infants with more body weight that received non-exclusive breastfeeding. The results of the hypothesis test using Chi-Square obtained a p-value of 0.006 (P<0.05). Conclusion: The early days of life are very important for infants regarding to their nutrition. Breastfeeding mother need support from the family thus the infants could get exclusive breastfeeding.